2008
DOI: 10.1007/s00216-008-2270-y
|View full text |Cite
|
Sign up to set email alerts
|

Analytical speciation of chromium in in-vitro cultures of chromate-resistant filamentous fungi

Abstract: In this work, different analytical speciation schemes have been used to study the reduction of Cr(VI) by a chromate-resistant strain of filamentous fungi Ed8 (Aspergillus sp), indigenous to contaminated industrial wastes. As demonstrated previously, this strain has the capability to reduce chromate present in the growth medium without its accumulation in the biomass, yet the reduced chromium end-products have not been characterized. Liquid growth medium, initially containing 50 mg L(-1) Cr(VI), was analyzed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…These observations indicated that in culture of the fungus a carbon source is required to provide the reducing power needed to decrease Cr (VI) in the growth medium. Our observations are like to the report of Acevedo Aguilar et al, Prasenjit and Sumathi [13, 24] with glucose like carbon source, and are different from the observations of Srivasta and Thakur [28] with Aspergillus sp, and Acinetobater sp, who observed how the main carbon source is the sodium acetate.…”
Section: Resultscontrasting
confidence: 77%
See 1 more Smart Citation
“…These observations indicated that in culture of the fungus a carbon source is required to provide the reducing power needed to decrease Cr (VI) in the growth medium. Our observations are like to the report of Acevedo Aguilar et al, Prasenjit and Sumathi [13, 24] with glucose like carbon source, and are different from the observations of Srivasta and Thakur [28] with Aspergillus sp, and Acinetobater sp, who observed how the main carbon source is the sodium acetate.…”
Section: Resultscontrasting
confidence: 77%
“…However, other yeasts such as Candida utilis [11] and Candida maltosa [12] showed partial ability to reduce Cr (VI) and also the capability to accumulate Cr in the biomass. Recent reports have also examined Cr (III) and Cr (VI) uptake and accumulation by different filamentous fungi [13, 14]. The present study reports the isolation and identification of a Paecilomyces sp.…”
Section: Introductionmentioning
confidence: 72%
“…Cr(VI) -resistant organisms are known to produce chromium reductase, which mediates the transfer of electrons from NAD(P)H to Cr(VI), converting it to Cr(III) [25,29,51]. The abilities of Aspergillus and Penicillium species to massively reduce Cr(VI) to Cr(III) have earlier been reported [26,[52][53][54][55].…”
Section: Cr(vi) -Reducing Activity Of Fungal Extractsmentioning
confidence: 99%
“…On the other hand, Cr(VI) is considered to be extremely toxic to organism since it has strong mutagenic and carcinogenic effects . Many researches have reported that Cr(VI) is harmful to organelle, protein, and nucleic acid , and the Cr(VI) exposure can cause allergies, eczema, stimulation, and respiratory disorders . Therefore, it is crucial to develop a sensitive and accurate analytical method for the quantification of different chromium species in foods and environment in order to ensure the human health.…”
Section: Introductionmentioning
confidence: 99%